Four‐Year Experience of Day Case Hemithyroidectomy: Patient‐Reported Outcomes. (2nd September 2014) - McCaffer, Craig J.; Douglas, Catriona M.; Kasbaker, Anand; Crosbie, Robin; Blaeco, David; Kang, Swee W.
Abstract : Objectives: Assess the safety, patient satisfaction, and outcome of day case hemithyroidectomy in our department. Methods: A prospective audit of all patients undergoing hemithyroidectomy in a single institution over a 3‐year period. All patients who undergo a hemithryoidectomy in our department have a bilateral superficial cervical block using 20 mL of 0.25% chirocaine, 10 mL of xylocaine with 1% adrenaline, and minimal opioid use. Bipolar dissection is used with meticulous hemostasis to avoid the use of a drain. All patients are reviewed 1 week postoperatively, and patient satisfaction questionnaires are completed. Results: One hundred fifty patients had a hemithyroidectomy over the 4‐year period. Average age was 49 years (21‐77). Male to female ratio was 3.9:1. Average length of stay was 0.47 days (0‐6). Eighty‐one percent of patients had their operation performed as a day case. The main reasons for patients not having surgery performed as a day case were patient choice, social reasons, and medical complications postoperatively. There were no hematomas requiring a return to theater and no drains inserted. No patient required readmission after discharge. Average patient satisfaction score for those discharged as a day case was 9.09 (0: not satisfied to be discharged as a day case ‐ 10: very satisfied to be discharged as a day case). Average pain score day 1 postop was 3 (0: no pain at all ‐ 10: worst pain imaginable). Conclusions: Day case hemithyroidectomy is very agreeable to patients and if appropriate analgesia is used then the postoperative pain is minimal.